ModelPS : an open-source and collaborative model edit platform with interactive transfer learning - Li, Yuanming (Nanyang Technological University, 2021)
Many applications are utilizing deep neural networks (DNNs) to provide intelligent services. However, due to frequent changes in the business requirements, developers often have to modify these DNNs, resulting in a massive cost in terms of monetary and time. To alleviate the issue, we propose a novel system, termed ModelPS (Model Photoshop), offering an interactive workspace for DNN editing.